Politics of language, ethnicity and identity in Zimbabwean ethnolinguistic online communities - Mpofu, Phillip (Taylor and Francis, 2021)
The language debate in postcolonial Africa is a contentious one. The dominant issues in extant scholarship include the supremacist position of English in Africa (Mazrui, 2004; Phillipson, 2010), the dominion of other African languages at the expense of other African languages (Ndhlovu, 2009) and the ascension of other dialects in standardised language varieties (Mpofu, 2013). In Zimbabwe, while speaking against the dominance of English is naturalised, overtly speaking against the dominance of other indigenous African languages or dialects is suffice to mean being political, tribal and at times retrogressive. Whilst the academic platform provides a “free” space for this volatile indigenous language debate, the public space is a restricted one. Therefore, in ordinary speech, the marginalised speech communities can only speak against their marginalisation and the marginalisation of their languages in secluded and classified settings. Regrettably, the press and broadcasting media have not done any better in challenging linguistic hegemony of whatever form or according the marginalised communities space to speak against their exclusion. Instead, they participate in legitimising such language practices (Mpofu, 2014).